2017
DOI: 10.3389/fpsyg.2017.01086
|View full text |Cite
|
Sign up to set email alerts
|

Supramodal Enhancement of Auditory Perceptual and Cognitive Learning by Video Game Playing

Abstract: Medical rehabilitation involving behavioral training can produce highly successful outcomes, but those successes are obtained at the cost of long periods of often tedious training, reducing compliance. By contrast, arcade-style video games can be entertaining and highly motivating. We examine here the impact of video game play on contiguous perceptual training. We alternated several periods of auditory pure-tone frequency discrimination (FD) with the popular spatial visual-motor game Tetris played in silence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…There have been limited investigations into cross-modality improvements among AVGPs. Tetris, a visual puzzle game, has been found to improve frequency discrimination and auditory working memory when play was interspersed with a frequency discrimination task 25 . Interestingly, auditory cognition and perception did not improve when the participants were exposed to the tetris stimuli without the gaming environment.…”
mentioning
confidence: 99%
“…There have been limited investigations into cross-modality improvements among AVGPs. Tetris, a visual puzzle game, has been found to improve frequency discrimination and auditory working memory when play was interspersed with a frequency discrimination task 25 . Interestingly, auditory cognition and perception did not improve when the participants were exposed to the tetris stimuli without the gaming environment.…”
mentioning
confidence: 99%
“…However, the introduction of these elements alone was insufficient to effect a significantly better outcome than the more traditional version. It has been previously shown that game-play can have an enhancing effect on perceptual learning, even where the video game is not directly related to the learning task, or indeed involving the same modality 34,40 . However, it may be that our “gamified” version was not sufficiently distinct from the standard task, since both versions provided performance-related feedback in form of “hits” and “misses” and, anecdotally, participants reported being quite motivated to improve over time whether they were using the gamified version or not.…”
Section: Discussionmentioning
confidence: 99%
“…Not only is gameplay engaging, having the potential to improve attention to a perceptual learning task, but it also leads to the release of reward signals such as dopamine 25 , which in turn have been purported to have an enhancing effect on perceptual learning through the promotion of synaptic plasticity in sensory processing nuclei 26 . The efficacy of video games to enhance various aspects of perceptual learning has been explored in the visual domain 27–30 and, more recently, in the auditory domain 31–34 . However, to what extent gamification can accelerate virtual sound localization training relative to a more traditional approach is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, different types of training tasks that share similarities with an untrained task can also improve performance in the untrained task (Beatty et al 2015; Berry et al 2010; Ortiz and Wright 2009; Wang et al 2016; Zhang et al 2016, 2017). These training tasks may not only result in enhanced sensory processing (Atienza et al 2002; Berry et al 2010; Ortiz and Wright 2009; Watanabe and Sasaki 2015) but may also improve high-level cognitive processes, such as working memory (WM), prediction, and attention (Beatty et al 2015; Siuda-Krzywicka et al 2016; Spence and McGlone 2001; Wang et al 2016; Zhang et al 2016), and these improvements may generalize to untrained tasks and stimuli.…”
Section: Introductionmentioning
confidence: 99%